Determining the Function Obtained from a Series of Transformations. Example #4 Find the function graphed after the following three transformations are applied to the graph of y = x . 1. Shift left 2 units y = x + 2 y = x + 2 + 3 2. Shift up 3 units. 3. Reflect about the y-axis y = -x + 2 + 3
Determining the Function Obtained from a Series of Transformations. Find the function graphed after the following three transformations are applied to the graph of y = x³. 1. Shift right 4 units y = (x – 4)³ y = (x – 4)³ - 1 2. Shift down 1 units. y = -(x – 4)³ - 1 3. Reflect about the x-axis